Chronic use of statins and acetylsalicylic acid and incidence of post‐endoscopic retrograde cholangiopancreatography acute pancreatitis: A multicenter, prospective, cohort study. Issue 4 (28th September 2020) - Cárdenas‐Jaén, Karina; Archibugi, Livia; Poropat, Goran; Korpela, Taija; Maisonneuve, Patrick; Aparicio, Jose R.; Udd, Marianne; Stimac, Davor; Arcidiacono, Paolo G.; De Pretis, Niccolò; Valente, Roberto; Di Giulio, Emilio; et al.
Abstract : Objectives: Post‐endoscopic retrograde cholangiopancreatography (ERCP) acute pancreatitis (PEP) is a frequent complication of this endoscopic procedure. Chronic statin intake has been linked to lower incidence and severity of acute pancreatitis (AP). Periprocedural rectal administration of non‐steroidal anti‐inflammatory drugs is protective against PEP, but the role of chronic acetylsalicylic acid (ASA) treatment is unclear. We aimed to investigate whether statins and chronic ASA intake are associated with lower risk of PEP. Methods: An international, multicenter, prospective cohort study. Consecutive patients undergoing ERCP in seven European centers were included. Patients were followed‐up to detect those with PEP. Multivariate analysis by means of binary logistic regression was performed, and adjusted odds ratios (aORs) were calculated. Results: A total of 1150 patients were included, and 70 (6.1%) patients developed PEP. Among statins users, 8.1% developed PEP vs. 5.4% among non‐users ( P  = 0.09). Multivariate analysis showed no association between statin use and PEP incidence (aOR 1.68 (95% CI 0.94–2.99, P  = 0.08)). Statin use had no effect on severity of PEP, being mild in 92.0% of statin users vs. 82.2% in non‐statin users ( P  = 0.31). Chronic ASA use was not associated with PEP either (aOR 1.02 (95% CI 0.49–2.13), P  = 0.96). Abuse of alcohol and previous endoscopic biliary sphincterotomy were protective factors against PEP, while >1 pancreatic guidewire passage, normal bilirubin values, and duration of the procedure >20 minutes, were risk factors. Conclusions: The use of statins or ASA is not associated with a lower risk or a milder course of PEP.